The esthetical values of Al-Amin from the aspects of Malay grammar and Arabic rhetoric - Adli Yaacob; Mohamad Shahrizal Nasir (Penerbit Universiti Kebangsaan Malaysia, 2010)
Of late, Islamic literature work has attracted great interest among fans of literature. This type of literary work which is related to Islam and its world view should be researched, so its benefits could offer every member of the society. Al-Amin written by Malaysian National Laureate, A. Samad Said, is currently the longest poetry ever written in the Malay language. An extensive period of time has been spent to complete this work, thus, this hard work should be appreciated not only by reading it, but also by discussing it academically for the benefit of the readers. Al-Amin tells of the entire life history of our beloved Prophet Muhammad p.b.u.h. and it encompasses a high esthetical value not only in the aspect of Malay grammar, but also in Arabic rhetoric. If referred to the discussion from an Arabic literature point of view, this poem can be categorized as the Panegyric Poetry of Prophet or the Poetry of Prophetic Biography. This article aims at introducing and promoting Al-Amin to the public, drawing attention to its literary values which play a major part in beautifying its contents. The article also shows some of esthetical values in Al-Amin from two angles, namely Malay grammar and Arabic rhetoric such as the use of assonance, alliteration, repetition, parable, quotation from al-Quran and Hadis and others. However, as this paper suggests, despite Al-Amin’s poetic and lyrical beauty, there are still many improvements that could be made for this poem.